2014
DOI: 10.1242/jeb.090902
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamics of the flying snake Chrysopelea paradisi: how a bluff body cross-sectional shape contributes to gliding performance

Abstract: A prominent feature of gliding flight in snakes of the genus Chrysopelea is the unique cross-sectional shape of the body, which acts as the lifting surface in the absence of wings. When gliding, the flying snake Chrysopelea paradisi morphs its circular cross-section into a triangular shape by splaying its ribs and flattening its body in the dorsoventral axis, forming a geometry with fore-aft symmetry and a thick profile. Here, we aimed to understand the aerodynamic properties of the snake's cross-sectional sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 71 publications
3
66
2
Order By: Relevance
“…Recently, some wind-tunnel experiments have been conducted to uncover the mystery of high-lift generation in the flying snakes. 12,13 It was found that the counter-intuitively high lift coefficients observed were attributable to the suction by the vortices on the dorsal side of the airfoil which has a snake-like cross-sectional shape. In a subsequent computational study, the enhanced lift was linked with the fact that the primary dorsal vortices were induced to remain close to the surface as a consequence of the interaction between the separated shear layer and the secondary vorticity.…”
Section: -2mentioning
confidence: 99%
“…Recently, some wind-tunnel experiments have been conducted to uncover the mystery of high-lift generation in the flying snakes. 12,13 It was found that the counter-intuitively high lift coefficients observed were attributable to the suction by the vortices on the dorsal side of the airfoil which has a snake-like cross-sectional shape. In a subsequent computational study, the enhanced lift was linked with the fact that the primary dorsal vortices were induced to remain close to the surface as a consequence of the interaction between the separated shear layer and the secondary vorticity.…”
Section: -2mentioning
confidence: 99%
“…One being the flying snake [47] the other being the question of whether some flights of birds invoke this principle? If one observes carefully the snake, on the co-published video [47], it seems to us that the snake is alternately letting its tail go over and under itself. Thereby it provides a 4π rotation which in principle could be continued indefinitely.…”
Section: Resultsmentioning
confidence: 99%
“…The lift is depending on the inclination of the relatively flat side of the snake as discussed in ref. [47]. The motion of the wings of birds is another candidate to be further investigated [48,49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Many different lineages of arboreal snakes have also convergently evolved variable abilities to form a ventrolateral keel (Figs 2, 3) (Smith, 1943;Wright and Wright, 1957;Pitman, 1974), which seems well suited for catching irregularities in tree bark and preventing slipping. However, unlike the consequences of cross-sectional shape for swimming (Graham et al, 1987;Aubret and Shine, 2008) and gliding (Holden et al, 2014), the consequences of variable crosssectional shapes for the locomotion of snakes on solid surfaces are poorly understood.…”
Section: Introductionmentioning
confidence: 99%